Potential pathogenic fungi assessment through molecular biology in cork industry - Viegas, Carla (2015)
Portugal has been the world leader in the cork sector in terms of exports, employing ten thousands of workers. In this working activity, the permanent contact with cork may lead to the exposure to fungi, raising concerns as potential occupational hazards in cork industry. The application of molecular tools is crucial in this setting, since fungal species with faster growth rates may hide other species with clinical relevance, such as species belonging to P. glabrum and A. fumigatus complexes. A study was developed aiming at assessing fungal contamination due to Aspergillus fumigatus complex and Penicillium glabrum complex by molecular methods in three cork industries in the outskirt of Lisbon city.